Rural land-use change key stakeholders network analysis in Shahriyar county, Iran - sara sadeghizadeh ghavi fekr; asghar tahmasebi; farhad azizpour (تحقیقات کاربردی علوم جغرافیایی)
Population growth and the need for economic and social services have accelerated the demands for land and its manipulations over the recent decades. The contribution of policies and interventions of different stakeholders in land change is not adequately addressed in previous studies. This research, therefore, aims to examine the role of key stakeholders, and their policies in land-use change in the study area. In doing so a total number of 20 interviews with senior experts and informants from 13 local organizations were conducted to collect qualitative data on the form, process and cause of land-use change in the area. Atlasti software was used to analysis the interviews' data. Furthermore, Social Networks Analysis (SNA) and questionnaires were used to map the trust among the stakeholders and also the role of their policies and program on land-use changes from the perspective of other stakeholders. The results show that the policies and interventions of the municipality are playing the most significant role in land-use change via disregarding and violations of roles and related for individual illegal benefits. Additionally, departments of agriculture, rural councils are among the most trusted agents in land use governance and management. Furthermore, water shortage was the most important reason pointed out by the many interviewees for conversion of farmlands to other uses. A part from water shortage, some other reasons such as: lack of governmental support for farming, strict official constraints and difficulties in providing amenities for gardens, expensive agricultural inputs, land price increase, immigration, corruptions in local organization are identified as drivers of rural land-use change. Keywords: Key words: Land use change, stakeholders, governance, Social Networks Analysis, Shariyar County.